ANALISIS PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI MUSEUM TEKSTIL JAKARTA - Asep Parantika; Muhammad Surya Saleh (BETRIK, 2024)
This study analyzes the content and sentiment of Jakarta Textile Museum's social media. to analyze the effectiveness of social media content and identify audience perception of Jakarta textile Museum's social media content. The method used is qualitative, data collection is carried out through observation of the textile Museum's social media activities, as well as related literature studies. The study aims to identify effective social media strategies, analyzes the challenges faced and provide recommendations to support increasing the number visits. The result of study from the analyzes of the content and sentiment of Jakarta textile Museum's social media promotion show that although there have been positive, there is still room for development in terms of audience interaction and engagement